(untitled) (TAJ: Journal of Teachers Association, 2011)
Background: In the tropics, leiomyoma are commonly encountered in women of the reproductive age group, although they are mostly asymptomatic. Surgery for uterine fibroid at caesarean section has remained controversial. Objective: The study design was a prospective multicentre study to analyse the clinical outcome of women that had selective caesarean myomectomy in a medical college and private hospitals in Dinajpur,Bangladesh. Method: Thirty women that had selective myomectomy at caesarean section between January 2004 and February 2012 were analysed. Results: The patients mean age was 32.6 years with age range of 21–39 years. Of the 30 patients, 21 (70 %) were Primigravida, 27 (90%) of the patients had caesarean section at term, 2 (6.6%) and 1 (3.3%) of the patients were preterm and post term respectively. A significant number of the patients 28 (93.4%) had elective caesarean section and the remaining 2 (6.6%) patients had emergency caesarean section. The 3 leading indications for caesarean section among the patients were malpresentation/abnormal lie 23%, uterine fibroids 26.6%, and a previous caesarean section with complication in 20% of the patients. Indications for myomectomy at caesarean section were fibroid in lower uterine segment in 18 (60%) patients, pedunculated uterine fibroid in 8(26.6%) patients and anterior subserous fibroid in 4 (13.3%) patients. Intraopertively in the 30 patients, 15 (50%) had fibroid(s) removed only in the lower uterine segment; while 7 (23.3%) patients had removed in the upper uterine segment and 8(26.6%) had both upper and lower uterine segments. A total of 75 fibroids were removed in the 30 patients, of which 40 (53.3%) were subserous/pedunculated, 25 (33.3%) intramural and 10 (13.3%) were submucous. Of the75 fibroids, 51 (68%) were between 6 to 10 cm size. Sixteen (53.3%) of the 30 patients lost between 751 to 1000 ml of blood intraoperatively with an average of 860 ml of blood loss. Five (16.6%) ofthe 30 patients had blood transfusion due to anaemia. Other complications encountered were puerperal pyrexia and sepsis in 2 (6.6%) patients. There was no maternal and perinatal mortality. Conclusion: Selection of patients for caesarean myomectomy reduces blood loss, anaemia and other complications. TAJ 2011; 24(1): 38-42